Recent Progress in Industrial Crystallization - Lorenz, Heike; Lewis, Alison Emslie; Temmel, Erik (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Crystallization is an important industrial process, a purification technique, a separation process and a branch of particle technology. It also encompasses the key areas of chemical and process engineering. industrial crystallization products include bulk chemicals such as sodium chloride and sucrose; fertilizer chemicals such as potassium chloride and urea; valuable products such as pharmaceuticals, platinum group metal salts, high grade materials for battery production and organic fine chemicals; engineered nanoparticles and crystals for the electronics industry as well as biotechnology products such as protein crystals. Industrial crystallization also encompasses the use of crystallization in water and effluent treatment. The overall theme of this Special Issue is how industrial crystallization is informed by the theoretical concepts of crystallization, and how practical understanding in the field is enhanced through applied research. The Special Issue is dedicated to Professor Gerda van Rosmalen who was a pioneer in this field. She developed the field of industrial crystallization research through her original approach and was regarded globally as a pre-eminent figure in the field. Additionally, this Special Issue provides a basis for the in-depth and comprehensive manuscripts of several oral poster contributions of ISIC 2021-held as an online event from August 30 to September 2, 2021.